The pattern of smartphone usage, smartphone addiction, and associated subjective health problems associated with smartphone use among undergraduate nursing students - Joyce Machado; Radhika R Pai; Reshma R Kotian (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The usage of smartphones has become common among adolescents, despite knowing the health-related problems of the user. Currently, the availability of electronic gadgets has become economical and this has an impact on society, especially on the behavior of adolescents. MATERIALS AND METHODS: A cross-sectional survey design was used to find the pattern of smartphone usage, smartphone addiction, and subjective health problems associated with smartphone usage. The data were obtained from 270 nursing students using the convenient sampling technique using a sociodemographic proforma, semi-structured questionnaire on the pattern of smartphone usage, Smartphone Addiction Scale, self-reported subjective health problems questionnaire, and study habits scale. STATISTICAL ANALYSIS: Descriptive and inferential statistics was used for the analysis using SPSS 16.0. RESULTS: The study findings revealed that most of the participants 243 (90.0%) were using 4G phones. The majority 88 (32.60%) of the participants were using a smartphone for less than 2 hours at a stretch in a day. Most uses of a smartphone were in the night 155 (57.40%). The main usage of a smartphone was for entertainment purposes 213 (78.90%). Most of the participants 196 (72.6%) were moderately addicted to smartphones. One-third 109 (40.2%) of the participants complained of headache, followed by straining of the eyes 83 (30.6%). CONCLUSION: The awareness of smartphone addiction and health-related problems associated with smartphone usage has been shown to decrease its impact. The study concluded that it is very much necessary to identify the pattern of smartphone usage, to prevent the consequences of addiction and health problems associated with smartphone usage.